ISLAMISASI MAMBI ABAD 17 - Hasriyodan; Dahlan; Susmihara; Herdian, Freddy (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) UIN Datokarama Palu, 2023)
This study aims to reveal the Islamization of Mambi in the 17th century with main focuses. first, the socio-political religious conditions of the Mambi people before the arrival of Islam; second, the pattern of acceptance of Islam in Mambi; third, the contribution of Islam to religious understanding. The authors use historical methods to reveal these historical events, including the following stages: heuristics or data collection, source criticism, interpretation, and historiography. The approach used in research; is history, politics, religion, and sociology. The results of this study, firstly, the socio-political condition of religion before Islam in Mambi, that the religion that becomes the belief of the community is Mappurondo or Mappurondo. Mappurondo cannot be separated from the social, political, and cultural pre-Islamic Mambi. So Mappurondo is a framework of rules that regulates human procedures in social life. Society in this case is governed by human relations with others, the universe, and the Creator, usually called Dehata. The rules are formulated in Pemali Appa' Randanna (four prohibitions). Pemali Appa' Randanna are rules regarding the four basic elements of the human life cycle. Secondly, the acceptance of Islam in Mambi in the 17th century was brought by a figure who had a very broad understanding of religion. The Mambi people know him by the name Batua Muhammad Adil. Third, the contribution of Islam to religious understanding until now has been abandoned by Pamali Appa' Randanna. Contribution to social politics until now the election of leaders is no longer done in a monarchical manner